The Syllabus Evaluation: Our Discovery Island 5–Student Book published by Pearson Education - Woro Endah Sitoresmi; Nina Afria Damayanti (JURNAL JENDELA PENDIDIKAN, 2022)
The success of English language subject is hardly required because the prior of language learning is communication. However, the success itself is not only based on the teacher, method, curriculum but also the package such as syllabus and textbook for delivering materials. Syllabus and textbook refer to the content of what is to be taught and the skills to be mastered. Furthermore, both of them help teacher to provide the materials well and to be relevant into the present context. The goal of this paper is to analyze deeply the English language syllabus design in Our Discovery Island 5–student book published by Pearson Education that is used by the elementary students of grade V in Citra Indonesia school, Bintaro. This study belongs to descriptive qualitative study. The findings show that the syllabus design in this book used the linear format to display the contents which include scope, sequence, integration, articulation and balance. Meanwhile for the syllabus model, it used process model on subject center design.